An = A1 x m (n - 1)
  where:
    A1 is the first term,
    An is the nth term (the term you are looking for)
    m is the number that each term is multiplied by to get the next term.
So, the 5th term of the first sequence above       (2, 4, 8, . . .) is:
A5 = 2 * 2(5-1) = 2 * 2(4) = 2 * 16 = 32
|
    Sum = A1 [ (1 - m n) / (1 - m)]
    A1 is the first term
    m is the number that each term is multiplied
        by to get the next term.
So, the sum of the first 4 terms of the first sequence above (2,4,8 ...) is
Sum = 2 (1-24)  / (1 - 2) =
            2 (1-16) / (-1) =
            2 (-15)   / (-1) = 2 x 15 = 30
            (2+4+8+16 = 30)
|